Semantic web for next generation of e-commerce - Kasmuria, Emaliana; Kannan, Subarmaniam; Woods, Peter (2006)
Web technology left a significant impact for business transaction.The role of buyers and vendors has been replaced by informative websites where the available information of products and services could improve supply chain and delivery cycles.As the market segment grows, the need of having organized and thoughtful web content is increasing.Search functions using keyword-based search are known for its inability for the machine to interpret different terminology with the same meaning.Information needs to be structured for parametric search to locate products with certain combination of traits.Ontology is the solution to structure semantic of product data.It allows computer to process content with meaning for human based consensual terminologies.Ontology provides a shared platform and common understanding of a domain that can be communicated between user and application systems.The purpose of this paper is to highlight the importance of exploiting ontology based e-commerce for Semantic Web. The ontology is mediator for software agents to communicate and exchange data.These agents can search products with certain traits, negotiate products or automatically configure product or services according to the required specifications.The semantic combination of product data elevate full potential of e-commerce and development of many specialized reasoning services bring full power of Semantic Web Based E-Commerce.